Advances in Candida albicans - Wang, Xinhui (Infectious Diseases, 2021)
Candida albicans, a fungal pathobiont, is the major component of the microbiota communities in healthy adults. It resides in the host's gastrointestinal tract and mouth and can become pathogenic via overgrowth under a variety of conditions. This book reviews recent knowledge and the latest research on C. albicans, including the mechanism of candidiasis infection, host response, antifungal strategies, biofilms, genetics, and molecular epidemiology of immune responses.